Etika Fuqaha’ Al-Salaf dalam Berbeda Pendapat Mengenai Masalah Fikih - Suraji, Suraji (Fakultas Syariah IAIN Purwokerto, 2010)
Differentopinion on Islamic law among Islamic scholars is such a relity and it also a part of God’s disposition that has to be taken wisely. Moslems ouht to learn and try to build a scientific athics that has been taught by fuqaha al-salaf. They taught about tolerance and respecting others opinins. Open mindedness is important to be learned to those different opinions. By learning those ethics, a peaceful and harmonious life might be realized.